The challenges of detecting and responding to a Lassa fever outbreak in an Ebola-affected setting. (January 2018) - Hamblion, E.L.; Raftery, P.; Wendland, A.; Dweh, E.; Williams, G.S.; George, R.N.C.; Soro, L.; Katawera, V.; Clement, P.; Gasasira, A.N.; Musa, E.; Nagbe, T.K.
Highlights: Lassa fever, a deadly infectious disease, is an epidemic threat needing urgent research and development action. An outbreak with a high case fatality rate occurring during the Ebola epidemic is described. Poor surveillance and response to early cases, a lack of timely specimen collection and transportation and limited treatment options were found. Strengthening the Integrated Disease Surveillance and Response system in West Africa is key to aid timely detection and response to outbreaks. Abstract: Objectives: Lassa fever (LF), a priority emerging pathogen likely to cause major epidemics, is endemic in much of West Africa and is difficult to distinguish from other viral hemorrhagic fevers, including Ebola virus disease (EVD). Definitive diagnosis requires laboratory confirmation, which is not widely available in affected settings. The public health action to contain a LF outbreak and the challenges encountered in an EVD-affected setting are reported herein. Methods: In February 2016, a rapid response team was deployed in Liberia in response to a cluster of LF cases. Active case finding, case investigation, contact tracing, laboratory testing, environmental investigation, risk communication, and community awareness raising were undertaken. Results: From January to June 2016, 53 suspected LF cases were reported through the Integrated Disease Surveillance and Response system (IDSR). Fourteen cases (26%) were confirmed for LF, 14 (26%) did not have a sample tested, and 25 (47%) were classified as not a case following laboratory analysis. The case fatality rate in the confirmed cases was 29%. One case of international exportation was reported from Sweden. Difficulties were identified in timely specimen collection, packaging, and transportation (in confirmed cases, the time from sample collection to sample result ranged from 2 to 64 days) and a lack of response interventions for early cases. Conclusions: The delay in response to this outbreak could have been related to a number of challenges in this EVD-affected setting: a need to strengthen the IDSR system, develop preparedness plans, train rapid response teams, and build laboratory capacity. Prioritizing these actions will aid in the timely response to future outbreaks.